2020
DOI: 10.3390/jcm9040904
|View full text |Cite
|
Sign up to set email alerts
|

Upstroke Time Per Cardiac Cycle as A Novel Parameter for Mortality Prediction in Patients with Acute Myocardial Infarction

Abstract: Background: Acute myocardial infarction (AMI) is one of the leading causes of death in the world. How to simply predict mortality for AMI patients is important because the appropriate treatment should be done for the patients with higher risk. Recently, a novel parameter of upstroke time per cardiac cycle (UTCC) in lower extremities was reported to be a good predictor of peripheral artery disease and mortality in elderly. However, there was no literature discussing the usefulness of UTCC for prediction of card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Chang LH et al also demonstrated that UTCC was associated with CV outcomes and in patients with type 2 diabetes 22) . Furthermore, our previous study revealed that UTCC was an independent predictor of long-term CV and all-cause mortality in patients with acute myocardial infarction 18) . According to the abovementioned literature 17,21) , UT and UTCC were useful parameters for the diagnosis of PAD and could be used to evaluate the peripheral vascular function and future outcomes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Chang LH et al also demonstrated that UTCC was associated with CV outcomes and in patients with type 2 diabetes 22) . Furthermore, our previous study revealed that UTCC was an independent predictor of long-term CV and all-cause mortality in patients with acute myocardial infarction 18) . According to the abovementioned literature 17,21) , UT and UTCC were useful parameters for the diagnosis of PAD and could be used to evaluate the peripheral vascular function and future outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…We adjusted significant variables and time to mortality using Cox regression analysis. We also calculated the improvement of global chi-square to evaluate the additive value of ABI, baPWV, LVEF, and UTCC over a basic model for long-term CV and all-cause cardiac cycle (UTCC) was reported to be a diagnostic tool of PAD and a predictor of mortality in patients with acute myocardial infarction and older population 17,18) . Therefore, our study aimed to evaluate the usefulness of UTCC for the prediction of CV and all-cause mortality in patients with normal ABI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Causes of CV mortality were defined deaths due to cerebral vascular disease, ischemic heart disease, myocardial infarction, heart failure, valvular heart disease and atherosclerotic vascular disease. The detailed method was the same as our previous published paper 18 .…”
Section: Methodsmentioning
confidence: 99%